Model Pembelajaran Talking Stick Berbantuan Media Audio Visual Terhadap Kompetensi Pengetahuan IPS Siswa Kelas V SD - Ni Putu Leny Purwani; Ni Wayan Suniasih (Journal for Lesson and Learning Studies, 2023)
Many elementary school students face difficulties in learning Social Studies (IPS) due to the extensive scope of the material. Additionally, IPS involves a significant amount of memorization. This research aims to analyse the Talking Stick Learning Model aided by audio-visual media on the competence of IPS knowledge. This study is quasi-experimental research with a non-equivalent control group design, and the population consists of 310 students. The sample selection in this research uses cluster random sampling technique. Data is collected using test methods. The testing of the instrument includes validity testing, reliability testing, differential power testing, and difficulty index testing. The data analysis technique in this study is inferential statistics. The average competence of IPS knowledge in the experimental group is higher than the average score of the control group (82.096 compared to 77.75). The results of data analysis using t-test indicate that the Talking Stick aided by audio-visual media has an influence on IPS knowledge competence. It is concluded that the Talking Stick aided by audio-visual media can improve the competence of IPS knowledge for fifth-grade elementary school students. The implication of this research is that the Talking Stick learning model aided by audio-visual.